Articulation between Family, Mathematics Education and Ancestry Tests in the school context (Research, Society and Development, 2025)
This article aims to understand the pedagogical implications of the articulation between Family, Mathematics Education and Ancestry Tests in the school context. The theoretical framework used is the Anthropological Theory of Didactics and the methodological framework adopted is action research. The praxeologies of a textbook and of the teacher are examined in a task that addresses percentages and graphic representations related to generational and genetic diversity. The study shows that the use of ancestry reports in teaching, combined with the active participation of families, can enrich mathematical learning by making it more contextualized, interdisciplinary and meaningful for students. However, the challenges of this approach are also discussed, such as the need for sensitive mediation in the face of possible identity tensions and inequalities in access to resources and knowledge. It is concluded that the integration between school, family and genetic data can expand the ecology of school praxeologies, favoring a more critical, humane and culturally situated mathematics education.